Islam and interfaith dialogue: the da'wah approach of Sayyid Abu al-Hasan al-Nadwi - Muhammad Uthman El-Muhammady, Asma (Bangladesh Institute of Islamic Thoughts (BIIT), 2018)
Using descriptive and analytical methods, this paper explores the role and contributions of an eminent SunnÊ scholar of the Indo-Pak subcontinent, Sayyid Abu al-×asan ‘AlÊ al-NadwÊ (d. 1420/1999) in promoting inter-cultural and religious dialogue between Islam and other faiths in the Hindu majority society, India. The study found that Nadwi adopted an approach whichcan be termed “moderate” butit was a strategic and unique approach in promoting and propagating da’wah in a difficult environment he lived in. To al-NadwÊ, living side by side with adherents of other religions is not only a challenge for Muslim minority as in India, but it also gives Muslims an opportunity to call others to the message of Islam. Besides, al-NadwÊ, like other SunnÊ scholars, was of the view that Islam is to be and can be practiced by Muslims at all levels of society regardless of the circumstances and environments in which they live in. Islam remains suitable for all situations of this spatio-temporal world. He also suggested that living religion (iqÉmat al-dÊn) in individual life is definitely a precondition for the success of Muslims which necessarily would lead to the improvement of their situation in the wider space in a non-Muslim majority context.